Involvement of brassinosteroids and ethylene in the control of mitochondrial electron transport chain in postharvest papaya fruit - Mazorra, Luis Miguel (2013)
The plant hormones brassinosteroids (BR) and ethylene (ET) act together to regulate plant metabolism. We used BR and 1-methylcyclopropene (1-MCP, an ET action inhibitor) to elucidate the interactions between both hormones for the regulation of mitochondrial respiratory pathways in papaya fruit. The exogenous application of the 24-epibrassinolide (epiBR) enhanced the alternative oxidase (AOX) capacity. While treatment with Brz2001 (Brz is a specific inhibitor of the BR synthesis) also enhanced AOX capacity, these effects lacked in fruit treated simultaneously with epiBR and Brz. Changing the BR level had no effect on ET emission rate in the first 24 h, but a reduction in ET emission was observed in Brz-treated fruit on the fifth day. Together with Brz, epiBR increased the ET production on the fifth day, following the day in which the treatment was carried out. When the ET sensitivity of fruit was inhibited by the application of 1-MCP, the effects of epiBR and Brz were opposite to those obtained without 1-MCP. AOX capacity was slightly inhibited by epiBR in fruit pre-treated with 1-MCP. Data suggest that BR and ET act antagonistically, therefore regulating, directly or indirectly, AOX capacity during papaya fruit ripening.